Miscellaneous information on Lagerstroemia L. (Lythraceae) - De Wilde, Willem J.J.O.; Duyfjes, Brigitta E.E. (Thai Forest Bulletin (Botany), 2014)
Lagerstroemia langkawiensis Furtado & Srisuko is a new record for Thailand. Lagerstroemia huamotensis W.J.de Wilde & Duyfjes (Thailand), Lagerstroemia kratiensis W.J.de Wilde & Duyfjes (Cambodia), and Lagerstroemia vanosii W.J.de Wilde & Duyfjes (Java) are described as new species, Lagerstroemia duperreana Gagnep. var. saxatilis W.J.de Wilde & Duyfjes as a new variety. The name Sibia DC. for a section as used by Furtado & Srisuko (1969) cannot be maintained, and the new section Parviflora W.J.de Wilde & Duyfjes is described to replace it. Important characters for species delimitation in Lagerstroemia are discussed.